JURIDICAL PROBLEMS ON COOPERATIVE BANK REGULATIONS ON INDONESIA'S ECONOMIC GOALS - Almaududi Almaududi; Ihsani Mazelfi (Jurnal Hukum dan Peradilan, 2022)
This paper is concerned with the juridical problems on cooperative banks’ regulations on Indonesia’s goals stated in the 1945 Constitution Republic of Indonesia. The problems arise due to the absence of commercial banks in the form of cooperative banks. Furthermore, Indonesia has a minimum number of cooperative rural banks (BPR Co). Currently, OJK registered only 19 BPR Co out of 1545 BPRs (0.01%). The study aims to examine the juridical problems of cooperative bank regulation in Indonesia’s goals as stated in the 1945 Constitution. It is normative research, analyzed qualitatively and presented in a descriptive. The study reveals that the Government and the Financial Services Authority (OJK) have no intention of further regulating the legal form of Cooperative Banks. We can see it from the non-accommodation of Cooperative Banks in Law on Syariah Banking. In addition, we could also see it from the absence of regulation on Cooperatives Commercial Bank in OJK Regulation. Therefore, it is not surprising that no commercial banks in Indonesia are in the legal form of cooperative.